The kiss of peace : ritual, self, and society in the high and late medieval West - Petkov, Kiril, 1964- (Cultures, beliefs, and traditions ;, 2003)
This text analyses the social logic of the mediaeval rituals of reconciliation as showcased by the potent rite of the kiss of peace. It shows that by using ritual and body mnemonics as strategic tools, the forces of order strove to organize personality structures around a hegemonic value system.